(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
Research on the circular economy has increasingly gained attention in recent years, focusing on promoting sustainable business practices and optimizing resource use. Nevertheless, studies on the circular economy in the context of agricultural products remain limited and require further exploration. Although previous findings suggest that agricultural derivative products can reduce waste, there is still no empirical evidence confirming whether these products meet community needs. This study introduces the Mapalus circular economy model for rural communities in Indonesia. The model addresses gaps in prior research by emphasizing the development of agricultural derivative products that are both community-oriented and value-added. It seeks to establish a production and consumption cycle within the community, thereby fostering a localized economic system that may enhance rural welfare. However, transforming village communities into both producers and consumers necessitates active participation, cooperation, and synergy. In this regard, the Mapalus tradition provides a foundation of collaboration grounded in kinship values.